SnPKS19 encodes the polyketide synthase for alternariol mycotoxin biosynthesis in the wheat pathogen Parastagonospora nodorum - Chooi, Y.; Muria-González, Mariano Jordi; Mead, O.; Solomon, P. (American Society of Microbiology, 2015)
© 2015, American Society for Microbiology.Alternariol (AOH) is an important mycotoxin from the Alternaria fungi. AOH was detected for the first time in the wheat pathogen Parastagonospora nodorum in a recent study. Here, we exploited reverse genetics to demonstrate that SNOG_15829 (SnPKS19), a close homolog of Penicillium aethiopicum norlichexanthone (NLX) synthase gene gsfA, is required for AOH production. We further validate that SnPKS19 is solely responsible for AOH production by heterologous expression in Aspergillus nidulans. The expression profile of SnPKS19 based on previous P. nodorum microarray data correlated with the presence of AOH in vitro and its absence in planta. Subsequent characterization of the ?SnPKS19 mutants showed that SnPKS19 and AOH are not involved in virulence and oxidative stress tolerance. Identification and characterization of the P. nodorum SnPKS19 cast light on a possible alternative AOH synthase gene in Alternaria alternata and allowed us to survey the distribution of AOH synthase genes in other fungal genomes. We further demonstrate that phylogenetic analysis could be used to differentiate between AOH synthases and the closely related NLX synthases. This study provides the basis for studying the genetic regulation of AOH production and for development of molecular diagnostic methods for detecting AOH-producing fungi in the future.